2010
DOI: 10.1177/0148607110374477
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Status and Risk Factors Associated With Length of Hospital Stay for Surgical Patients

Abstract: LOS was associated with disease and nutrition status. Among the more common diseases, nutrition status according to the subjective approach determined the LOS for patients with DTD and nutrition status according to arm circumference determined the LOS for patients with neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 25 publications
4
56
0
1
Order By: Relevance
“…For many years, many studies have reported undesirable outcomes that may occur during the hospital stay of patients diagnosed with malnutrition or even at some nutritional risk (28,31) . These findings have been observed in patients with neoplasms, digestive tract diseases, and other clinical situations (22,24,31) .…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…For many years, many studies have reported undesirable outcomes that may occur during the hospital stay of patients diagnosed with malnutrition or even at some nutritional risk (28,31) . These findings have been observed in patients with neoplasms, digestive tract diseases, and other clinical situations (22,24,31) .…”
Section: Introductionsupporting
confidence: 53%
“…The individual energy requirement was estimated by the equation proposed by Harris & Benedict (17) . This method has already been described in other studies (22) . Later, HEI was expressed as a percentage of the energy requirement.…”
Section: Assessment Of Habitual Energy Intake (Hei)mentioning
confidence: 99%
See 3 more Smart Citations